Perancangan Sistem Informasi Penjualan Berbasis Java Pada Toko Rumbur Exotic Pet - Muhammad Tri Habibie (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
As a beginner in the business of exotic animals provider, Rumbur Exotic Pet run the business activities manually and do not utilise advanced technology, so it’s performance is less effective and efficient. Therefore, adequate technological support is needed to improve business performance and productivity through designing a Java-based sales information system. This research use the Waterfall model as one of the SDLC (System Development Life Cycle) software development methods. The system design tools that used are Data Flow Diagrams (DFD) and Entity Relationship Diagrams (ERD). The results of designing a Java-based sales information system can increase work effectiveness and efficiency, facilitate data collection and storage of sales information, produce detailed and accurate reports, and encourage productivity and profitability.